2020
DOI: 10.1177/1369433220963728
|View full text |Cite
|
Sign up to set email alerts
|

Vibration control by active integrated control system under bidirectional ground motions

Abstract: To improve the safety and security of the structures with irregular plan configuration, the new torsionally effective passive control system (ICS) was first proposed by the author, which utilizes a new design configuration to dissipate the unwanted energy from the structures in the lateral and torsional directions. In this research, a new active structural control approach, which is the active form of the ICS (or active integrated control system, AICS), is introduced as an alternative active control system, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…An active integrated control system was proposed by Akyürek and Suksawang. 17 They showed that the proposed method was effective in response control of buildings under bidirectional ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…An active integrated control system was proposed by Akyürek and Suksawang. 17 They showed that the proposed method was effective in response control of buildings under bidirectional ground motions.…”
Section: Introductionmentioning
confidence: 99%